A LOOK AT JUSTICE CONDITIONS ON DIFFERENT IRANIAN ETHNICS IN ISLAMIC REPUBLIC OF IRAN’S CONSTITUTION (BASED ON DISTRIBUTIVE JUSTICE) - KHALAF, MASOUD EMADI; ABBAS, ALI POUR (Innovare Journal of Social Sciences, 2023)
Iran is a multiethnic country including various ethnic, linguistic, and religious groups. Persians, Azeris, Turkomans, Kurds, Lors, Baluchis, and Arabs as the well-known ethnics of Iran are scattered throughout geography of Iran. Constitution as a supreme law with a main purpose of providing justice illustrates distributive justice in different articles including the articles 15, 19, 20, 28, 29, 30, 31, and 43 and regards all the Iranians equal share for possession of economic and social rights. Distributive justice esteemed as social-economic justice is a concept whose background refers to the old history and in a modern concept; it seeks the government guarantee for distribution of country’s wealth throughout the whole community in a manner that all the citizens hold a certain value of worldly facilities concerning their rights. The current descriptive-analytic study having been performed in the context of library research is performable in terms of purpose, because it’s findings could be effective in the decision and policy making. This research seeks to answer the significant question that whether the distributive justice of Iran’s ethnics is of any importance to the constitution of Islamic Republic of Iran or not. According to the results of this work, despite the stipulation of equality principle by constitution, distributive justice of Iran’s ethnics is not performed except for some cases. Besides, the constitution lacks the required explicitness and includes some ambiguities.